Grammatical Error Analysis in Recount Text Made by the Students of Cokroaminoto University of Palopo - Hermini Hermini (Ethical Lingua: Journal of Language Teaching and Literature, 2015)
This study aimed to find out (1) Grammatical errors in recount text made by the English Department students of the second and the sixth semester of Cokroaminoto University of Palopo, (2) the frequent grammatical errors made by the second and the sixth semester students of English department students (3) The difference of grammatical errors made by the second and the sixth semester students. The sample of the study was 723 sentences made by 30 students of the second semester and 30 students of the sixth semester students in academic year 2013/2014 that were taken by cluster random sampling technique. The sentences were 337 (46.61%) simple sentences, 83(11.48%) compound sentences, 218 (30.15%) complex sentences, 85 (11.76%) compound complex sentences. The data were collected by using two kinds of instruments namely: writing test to find the students’ grammatical errors and questionnaire to find the solution to prevent or minimize errors. Data on the students’ errors were analyzed by using descriptive statistics. The results of the study showed that the students made 832 errors classified into13 types of errors which consisted of 140 (16.82%) errors in production of verb, 110 (13.22%) errors in preposition, 106 (12,74%) errors in distribution of verb, 98 (11.77%) miscellaneous errors, 82 (9.85%) errors in missing subject, 67(8.05%) errors in part of speech, 61 (7,33%) errors in irregular verbs, 58 (6.97%) other errors in verb groups, 52(6.25%) errors in the use of article, 24 (2.88%) errors in gerund, 18 (2.16%) errors in infinitive, 11(1.32%) errors in pronoun/case, and 5 (0.6%) errors in questions. The top six frequent grammatical errors made by the students were production of verb group, preposition, distribution of verb group, miscellaneous error, missing subject, and part of speech. The difference of both groups was the frequency in committing errors such as part of speech, irregular verb, infinitive verbs, and other errors in verb.